PENERAPAN SISTEM KAWIN SODOK DAN MESIN TETAS MENINGKATKAN PRODUKTIVITAS AYAM BURAS SEBAGAI HEWAN UPAKARA DI DESA JIMBARAN - Wirapartha M; K.A. Wiyana; W. Wijana; G.A.M. Kristina Dewi; K. Karnama (Buletin Udayana Mengabdi, 2012)
This community service was conducted under the litle “Aplication Of Hand Breeding Systems and Hatching Machine Tecnology in an Effort to Reduce Raising Costs and Improve Productivity of Domestic Chicken (Buras Chiken) as Ceremony Poultry in Jimbaran Village” on Friday, September 16 , 2011. Education and training aims to improve knowledge and skills of raisers in the village of Jimbaran in intoducing and applying hand breeding system and use of technology in domestic poultry hatching machine. In achieving this goal, the methodes used by 1) providing information about the hand breeding system to domestic chiken , hatching machine technologi and its benefits, 2) training on how to use hand breeding system to domestic chiken and use of hatching machine correctly and practically, 3) giving assistance in the form of papers on the management of the use of hatching machines, providing hatching eggs, chiken hatching machine, observation of chicken eggs, chicken hatching machine, observation of chicken eggs, roosters and hens. The result of this training with 40 participants was very good. All participants who were present, as people in Br. Mekar Sari Simpangan, Jimbaran Village, Bandung had never seen this system before and never applied the breeding system and hatching machine technology. People were very enthusiastic, it was proven from the questions asked and in general the participants were able to understand such technology on how to use hatching machine and the hand breeding system in domestic poultry.